Molecular classification of diffuse gliomas - Jakovlevs, Arvids; Vanags, Andrejs; Gardovskis, Janis; Strumfa, Ilze (Polish Journal of Pathology, 2019)
In this study we assessed whether gliomas could be subdivided into different molecular subtypes by immunohistochemistry (IHC) reminiscent of those first described by Verhaak et al. in 2010 (classical, proneural, mesenchymal and neural). We also evaluated the prognostic significance of single molecular factors and searched for significant correlations between markers. In this study, we included 146 patients with glioblastomas (GBMs) and 26 with diffuse astrocytomas (DAs). The glioma samples were tested for PDGFRA, IDH1 R132H, CD44, p53, Ki-67, p21 and p27 expression. We found that gliomas could be subdivided into molecular subtypes by IHC. Fifty per cent of GBMs were of the proneural subtype, 18.5% of mesenchymal subtype and 31.5% were not otherwise classified. However, most of the DAs (92.3%) belonged to the proneural subtype. No prognostic role was found for the molecular subtypes, but predictive roles were noted. Both proneural and mesenchymal molecular subtypes showed a benefit from the addition of chemotherapy and radiotherapy; however, the mesenchymal subtype showed a greater response. Interestingly, the mesenchymal subtype did not receive any benefit from the addition of radiotherapy compared with palliative management and surgery alone. Regarding single molecular markers, only IDH1 R132H was found to have a prognostic role for GBMs. There was a trend towards better survival in tumours with lower PDGFRA expression (p = 0.066). In DAs, PDGFRA and Ki-67 expression had prognostic roles. The following statistically significant correlations were found in GBMs: Ki-67/p53, Ki-67/p27 and p53/PDGFRA; in DAs: p53/PDGFRA, CD44/PDGFRA, and p21/PDGFRA.